Use of ICT for process re-engineering and structural transformation of national institute of open schooling - Bist, Dinesh Singh (2009)
National institute of Pen Schooling (NIOS), formerly known as National Open School, is an autonomous organisation under the Ministry of Human Resource Development (MHRD), Government of India, was set up in November 1989. Its three fold mission is to assist Government of India in achieving its goal of Universalisation of Education in promoting greater equity and justice in society and helping in evolution of learning society by providing relevant, continuing and development education upto the pre-degree level through open distance system through its prioritised group as an alternative arrangement to formal school system. In short its one line charter is to reach the "unreached" comprising of school drop outs, rural youth, urban poor, Scheduled Castes and Scheduled Tribes, Minorities and other sections of society, who have been left out of the mainstream formal school system. - Reproduced.
Keywords: Schools; Communication technology; Information technology